Enhancing Bird’s Eye Chili (Capsicum frutescens) Productivity Through Combined Application of Eco-Enzyme and Trichoderma viride - Sheina Revania Putri Doo; Sri Kasmiyati; Samse Pandiangan; Siti Nur Hidayati; V. Irene Meitiniarti (Universitas Negeri Semarang, 2026)
Bird’s eye chili (Capsicum frutescens L.) is a high-value horticultural crop, yet yields in Indonesia remain low due to long-term use of chemical fertilizers, which reduce soil fertility. Organic fertilizer alternatives, such as eco-enzyme and Trichoderma viride, offer potential for sustainable agriculture. This research aimed to study the impact of eco-enzyme and T. viride, applied individually and in combination, on the growth and yield of Bird’s eye chili, as well as on soil N, P, K, organic carbon, and IAA levels. The study employed a Completely Randomized Design (CRD) with four treatments: control, eco-enzyme, T. viride, and a combination of eco-enzyme and T. viride, each with eight replications. The research was conducted in a polybag over 20 weeks. Parameters observed were plant height, leaf number, root length, number of flowers and fruits, fruit weight, and soil N, P, K, C-organic, and IAA. Compared with the control treatment, the application of eco-enzyme and T. viride improved several growth and soil quality parameters. The combined treatment increased vegetative growth and enhanced soil N, P, K, and IAA contents, whereas T. viride alone produced the highest fruit yield. These results suggest that eco-enzyme and T. viride can be used as biological inputs to improve chili production while helping maintain soil fertility and reduce dependence on chemical fertilizers. The findings are relevant to SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land), particularly regarding sustainable food production, resource recycling, and soil conservation.